Exploring the triadic parent–child–sibling relationship: How do mothers' view of their children impact sibling relationships?. Issue 2 (5th May 2023) - Drzymala, Hannah; Grey, Ben; Fowler, Nancy
The functioning of the sibling subsystem is often overlooked in research on attachment relationships, despite its both threatening and protective potential. Taking a multi-case approach, this study sought to build theory regarding how the mother–child relationship and the mother's view of each of her children impact the sibling relationship. Three families were assessed using the Meaning of the Child Interview, a method of analysing parental discourse in a semi-structured interview to understand the parent–child relationship, and a sibling free-play procedure. The study illustrated how in more struggling relationships, the child represented a particular threat or challenge to the mother, and how the child's accommodation to this influenced the dynamics of the sibling relationship. The sibling may be recruited to care for their sibling to ease demands on their mother, serve as an ally with their mother against their sibling, or siblings may support each other to compensate for what is lacking in the child–parent relationship. This was further influenced by wider systemic challenges to both children and mother, such as parental conflict or settling in a new country.